EVALUASI KUALITAS LAYANAN PERAWATAN KESEHATAN DI RUMAH SAKIT I.A MOEIS (PEMERINTAH) DAN RUMAH SAKIT DIRGAHAYU (SWASTA) SAMARINDA DENGAN METODE SERVQUAL PADA MASA PANDEMIC COVID 19 - Sholikah, Imroatus; Widyarto, Widyarto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: According to (Holbrook, 2012) measuring the success of public services provided should use the point of view of the user community in an effort to assess how the wishes expected by the community in their view of a service provided are able to provide the satisfaction they want. Service quality and customer satisfaction are very important components of competitive advantage in the health care sector. (Nasullah, 2020), (Suliswanto, 2020) The SERVQUAL method is widely used to assess the quality expected by patients and the quality of service actually provided, especially during the covid 19 pandemic (Hidayat, Kristanto and Eka, 2020), (Nasution, Erlina and Muda, 2020) with limited officers who use personal protective equipment that limits movement and activities can reduce service quality where one indicator of customer satisfaction is service with a smile (Seder and Oishi, 2012), (Chang et al., 2011), (Van Der Geld, 2011), 2011), (Van Der Geld et al., 2007), (Söderlund and Rosengren, 2008), (Otterbring, 2017) which are not visible because they are covered by masks, words that are not clearly audible and distances that are not clear. In addition, there is a fear of the public to visit or seek treatment at the hospital for fear of contracting the covid 19 virus (Moh, 2020), (Zendrato, 2020) or being diagnosed irrationally or baselessly where those who previously suffered from diseases that were not covid but would be diagnosed with covid 19 (Singh et al., 2020) '(Kanneganti et al., 2020) '(Ramaci et al.. 2020) because they have symptoms similar to covid 19 starting from this, researchers are interested in knowing the quality of service between the two hospitals, namely the I.A Moeis Samarinda Hospital which is managed by the government and the Dirgahayu Samarinda Hospital, 2020) because it has symptoms similar to covid 19 starting from this, the researcher is interested in knowing the quality of service between the two hospitals, namely the Samarinda I.A Moeis Hospital which is managed by the government and the Dirgahayu Samarinda Hospital which is managed by the private sector, whether there are differences in the level of satisfaction between the two hospitals and to find out each level of customer satisfaction about the health services provided. This type of observational analytic study used a cross-sectional design. This study involved a total plan of 200 patients: 100 admitted to government facilities and 100 admitted to private facilities taken by random sampling Respondents were asked to fill out a questionnaire after they gave their consent and with the criteria of having visited / treated more than 2 times Each respondent completed 5 domains, 22 items of the SERVQUAL questionnaire. Bivariate data analysis techniques using Mann-whitney and linear regression. The results showed a ρvalue = 0.000 with a confidence level of 95% and dk = 2. Thus, ρvalue (0.000) < α (0.05) indicates a difference in the level of patient satisfaction with services in government hospitals and private hospitals.Keywords: Patient Satisfaction, Hospital.